Multiple evaluations, risk assessment, and source identification of heavy metals in surface water and sediment of the Golmud River, northeastern Qinghai-Tibet Plateau, China - Cai, Na; Li, Leiming; Zhu, Haixia; Chen, Liang; Li, Shanping; Meng, Fanwei; Zhang, Xiying (Frontiers in Environmental Science, 2023)
The water quality of the Golmud River is essential for environmental preservation and economic growth of Golmud city and Qarhan Salt Lake in China. Thirty-four samples of surface water and sediment from seventeen places in the Golmud River and thirty-two dustfall samples in the Qaidam Basin were collected. The concentrations of heavy metals (HMs) were measured; water quality, risk assessment, and multiple source analysis were applied. Concentrations of HMs in water were Zn>Cu>Ni>As>Pb>Cd> Hg, and in sediment were Ni>Zn>Pb>As>Cu>Cd>Hg. In water, the Nemerow pollution index (NP) values indicated that most of the sampling points seemly were seriously polluted; other water quality assessment results suggested no pollution. In sediment, the concentrations of 27% HMs exceeded the background values of soil in Qinghai; 48% exceeded the earth crust background values, which were As, Hg and Cd. The single factor index method (Pi), geological accumulation index (Igeo), and contamination factor (CF) revealed that As pollution is serious, followed by Hg and Cd; the pollution load index (PLI) and modified pollution index (mCd) values indicated that 64% and 57% of samples were polluted. NP values are shown serious pollution. The ecological risk results demonstrated a low risk in water and a medium risk in sediment. The average total hazard quotient values in sediment and water for adults and children revealed low non-carcinogenic risks. Carcinogenic risk indicated Ni in water and sediment, and As in sediment may be involved in cancer risk. Multivariate statistics showed that the HMs mainly came from nature, and human activities will also impact them. The upper continental crust values indicated that As and Hg have high background values. The saline dust storm was one of the essential sources of HMs, especially Hg. Various provenances constituted the material cycling of HMs in the surface environment.